2012
DOI: 10.3998/ark.5550190.0013.332
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of 6-mercapto-6H-dibenzo[c,e][1,2]oxaphosphinine 6-sulfide

Abstract: The synthesis route of the novel 6-mercapto-6H-dibenzo[c,e][1,2]oxaphosphinine 6-sulfide 4 from 6-chloro-6H-dibenzo[c,e][1,2]oxaphosphinine 1 and its spectroscopic investigation are presented. In addition, reaction of the thiol group with unsaturated functionalities such as acrylates demonstrated that the newly synthesized compound could undergo thiol-ene chemistry. Moreover, modification of the reaction condition led to the formation of the rearrangement product of a thiol-Michael reaction of compound 4 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Good availability of dithiophosphinic acids 3 and 6 as starting materials enables a broad variety of subsequent reactions. Recently, the Michael -like addition of 3a to different acrylates as well as benzoquinone was reported . Also the preparation of bis(diphenylphosphinothioyl) disulfide has been investigated, and different synthetic approaches have been reported. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Good availability of dithiophosphinic acids 3 and 6 as starting materials enables a broad variety of subsequent reactions. Recently, the Michael -like addition of 3a to different acrylates as well as benzoquinone was reported . Also the preparation of bis(diphenylphosphinothioyl) disulfide has been investigated, and different synthetic approaches have been reported. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the synthesis of 3a via sulfidation of 6-chloro-6H-dibenzo[c,e]- [1,2]oxaphosphinine (1) to form 6-chloro-6H-dibenzo[c,e]- [1,2]oxaphosphinine 6-sulfide (2) and its subsequent conversion with elemental sulfur and triethyl amine (route A, Scheme 1) has been described. 14 However, it has now been found that the initial sulfidation of 1 does not necessarily need to be carried out in a separate reaction step. Instead, feasibility of a one-pot reaction was demonstrated which is advantageous with respect to synthetic effort and reaction time (route B, Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOPO and its derivatives contain benzene ring structure in their molecular structure and have higher thermal and chemical stability and better flame-retardant performance than ordinary, uncycled organophosphate. Rakotomalala [24][25][26] synthesized 9,10-dihydro-9-oxa-10-phosphate-phenanthrene-10-sulfide (DOPS) for the first time in 2011, and it has been reported that the introduction of sulfur into the structure of DOPO by replacing the P S bond with the P O bond through a thiolation reaction not only increases the reactivity of the P H bond and facilitates the generation of a variety of DOPS derivatives, but also enhances the flame-retardant effect of phosphorus, which is more prone to synergistic flame-retardant effects. 27 Moreover, during the combustion process, the sulfur compounds in DOPS decompose and release strong acids such as H 2 SO 4 under the catalytic effect of high temperature, which promotes the dehydration of EP into char, and the dense expanded char layer can effectively isolate the external oxygen exchange, which makes up for the single gas-phase flame-retardant mechanism of DOPO, and exerts an excellent flame-retardant effect in the condensed phase.…”
Section: Introductionmentioning
confidence: 99%